The impact on sales of internet plans in a company in the municipality of Vila Velha in the COVID-19 scenario - Santos , Emanuella Claudino Alves; Almeida, Miriam Aparecida Ignácio de; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2022)
The Covid-19 pandemic has spread throughout the world, changing the routine of today’s society and causing changes, new habits and new needs. Professional and educational activities started to be performed remotely at a distance, therefore, one of the services that had its highlighted importance was the provision of internet plan services. The present study aims to understand how the Covid-19 scenario impacted sales in an internet plan service provider, in this work called company x, from the action research method where the volume history will be verified. 2018-2021 year sales figures and plans sold and updated in this scenario.